Ameliorative effects of apigenin on a rat model of endometriosis - Hekimoğlu, Gulam; Koç, Sümeyye; Daştan, Ali İmran; Şevgin, Kübra; Tekayev, Muhammetnur; Güler, Eray Metin; Sayir, Neslihan; Canbaz, Halime Tuba; Hacımustafaoğlu, Fatih; Pence, Halime Hanim; Sapmaz, Tansel; Kale, Ebru (The European Research Journal, 2023)
Objectives: Apigenin and parthenolide as natural products have potent antioxidant and anti-inflammatory outcomes that could make them a perfect option for endometriosis therapy. This study aimed to determine the effects of apigenin and parthenolide on created endometrial implants in a rat model of endometriosis. Methods: Thirty-nine mature, female Sprague-Dawley rats were assigned randomly to six experimental groups four weeks after endometriosis induction. Group 1 (n = 5): Control (CTRL) that opened and closed the abdomen; Group 2 (n = 6): Peritoneal and ovarian endometriosis (POE) + drug-free; Group 3 (n = 7): POE+ Apigenin (APG) (50 mg/kg); Group 4 (n = 7): POE+ Parthenolide (PTL) (10 mg/kg); Group 5 (n = 7): POE+ Apigenin (APG) (50 mg/kg) + Parthenolide (PTL) (10 mg/kg); Group 6 (n = 7): POE+ DMSO. An endometriosis model was created, and histopathological analysis and biochemical evaluation were performed. Serum and peritoneal levels of pro-and-anti-inflammatory cytokine, and oxidative stress of implant tissue were measured. Results: Serum IL-37 levels decreased significantly in the APG-treated group compared to the drug-free group (p = 0.016). The peritoneum and ovary endometriosis histopathologic scores were significantly lower in APG-treated (p = 0.001) and PTL-treated (p = 0.001) groups in comparison to the drug-free group. The oxidative stress index (OSI) values were increased statistically significantly in ovary endometriosis tissue in the drug-free group, (p = 0.001). However, compared to the drug-free group, OSI values decreased statistically significantly in the APG-treated group (p = 0.003).Conclusions: The application of apigenin caused a decrease in oxidative stress and an improvement in histopathological grade. Apigenin may be a novel therapeutic agent for the treatment of endometriosis.